Desempenho profissional do psicólogo escolar: relação entre conhecimento da amplitude de suas funções e limites institucionais - Salles, Regina Celi Muniz de (1984)
This paper had its origin in the need for a systematic approach to the numerous questions which have arisen concerning the efficiency of School Psychology -questions which appear to underestimate its vital importance in the Brazilian educational context. Whe have tried to rethink critically the work done by psychologists in our schools, often without much reference to the underlying objectives of the institution and as a mere spectator of the way the institution functions. Thorough analysis of these questions called for an epistemological approach, focused on construction of the 'real', as approached through the 'possible' and the 'necessary' in education. A research project was carried out which involved 33 psychologists from private schools. It was aimed at analysis of their functions, in order to diagnose their limitations and possible causes of these, as well as the scope of their proposals for action. Hypotheses are advanced in this paper which might lead to a better understanding of the reasons which have led school psychologists to perform their functions, either 'institutionally' or 'clinically' in the educational context. Results show that 67% of school psychologists know the extent of their functions and try to fulfil them completely in spite of restrictions imposed by the institution, although they are aware that their work is more closely linked to institutional aspects. An investigation was made in thirty-four schools, whether they had school psychologists or not, to find out why head teachers employ a psychologist. According to the schools which have a psychologist, 54% of the head teachers employ a psychologist because they think his work important, whereas 22% do so because of the status of the school. As to those schools which have no psychologist, 75% have already felt the need to engage one, although 50% have taken no action, because of economic conditions, and 50% because the educational adviser meets the school's needs. The results indicate that the better the school psychologist understands and assumes the full scope of his functions the more readily he will be able to cope with the problems and difficulties of the institution, once he sees from analysis of possibilities and needs in the institutional context how to make the construction of an educational 'reality' possible. In so far as the school psychologist assumes his professional identity, he will open up new professional rerspectives and room for development within the school institution itself.